Effect of the addition of conventional additives and whey proteins concentrates on technological parameters, physicochemical properties, microstructure and sensory attributes of sous vide cooked beef muscles - Szerman, Natalia; Gonzalez, Claudia Beatriz; Sancho, Ana Maria; Grigioni, Gabriela Maria; Carduza, Fernando Jose; Vaudagna, Sergio Ramon (Elsevier, 2019)
Beef muscles submitted to four enhancement treatments (1.88% whey protein concentrate (WPC) + 1.25% sodium chloride (NaCl); 1.88% modified whey protein concentrate (MWPC) + 1.25%NaCl; 0.25% sodium tripolyphosphate (STPP) + 1.25%NaCl; 1.25%NaCl) and a control treatment (non-injected muscles) were sous vide cooked. Muscles with STPP + NaCl presented a significantly higher total yield (106.5%) in comparison to those with WPC/MWPC + NaCl (94.7% and 92.9%, respectively), NaCl alone (84.8%) or controls (72.1%). Muscles with STPP + NaCl presented significantly lower shear force values than control ones; also, WPC/MWPC + NaCl added muscles presented similar values than those from the other treatments. After cooking, muscles with STPP + NaCl or WPC/MWPC + NaCl depicted compacted and uniform microstructures. Muscles with STPP + NaCl showed a pink colour, meanwhile other treatment muscles presented colours between pinkish-grey and grey-brown. STPP + NaCl added samples presented the highest values of global tenderness and juiciness. The addition of STPP + NaCl had a better performance than WPC/MWPC + NaCl. However, the addition of WPC/MWPC + NaCl improved total yield in comparison to NaCl added or control ones.